Agricultural Interventions and & Sustainability of Rural Livelihoods: A Case of Rural Women Potatoes Production Farmers Groups in Njoro Sub-county Kenya. - Wambu, Charles (Machakos University, 2019)
Women play indispensable role in agriculture and in improving the quality of life in rural areas. However, their contribution often remains concealed due to some social barriers and gender bias. This study assessed the adoption of Agricultural Innovations among rural women farmers in Njoro sub-county. To achieve this major objective, the study identified the socio-economic characteristics of the respondents as well as agricultural innovations introduced and their extent of use. Also the study determined the effects of technologies used on agricultural production. The study adopted cross-sectional study survey with concurrent mixed methods approach entailing equal preference to quantitative and qualitative methodologies to generate rich information that helped fully to explore each of the survey objectives. The respondents were sampled using different approaches for quantitative and qualitative aspects of the survey. For quantitative segment, simple random sampling was done to identify beneficiaries’ households (HHs) for the household survey. The survey target 240 farmers who were organized into 2 clusters of 12 farmer groups (Each cluster 6 groups) comprising of 20 farmers each working as a production group in Mauche and Mau-Narok divisions in Njoro sub-county, Nakuru County, Kenya. The sample size representative of the farmers in this study was 148. Primary data collected using a combination of quantitative and qualitative methods including group discussion, structured interview, semi structured interview, Key informant Interviews (KII) and some PRA tools such as Venn diagram, Gender Analysis Matrix, and Time Trends. Secondary sources comprised of relevant project documents and State and Non-state partner reports. The data collected was analyzed using qualitative and quantitative methods with the help of Statistical Package for Social Science (SPSS). The study findings revealed their was positive and significant relationship between the constraints encountered and adoption level of Agricultural Innovation. It was also revealed that late adoption of innovations was due to irregular visits of extension agent. The major constraint revealed in the study was unstable market price, which has seriously affected the women’s activities. Therefore the study recommends that the government should enforce price stabilization policies which will control market prices so as to reduce shortage and losses.
Keywords: Agricultural Interventions Sustainability& Rural Livelihoods